Congenital urethrocutaneous fistula: Case report with review of literature - Ankur Bhatnagar; Vijai Upadhyaya; Basant Kumar (Indian Journal of Plastic Surgery)
We are presenting two cases of congenital urethrocutaneous fistula on ventral penile shaft. Congenital urethral fistula is an extremely rare, but easily manageable anomaly that may be confused with hypospadias. Awareness of the entity will avoid complications. This condition may be associated with other anomalies like congenital hernias and anorectal malformations. Treatment of this entity is individualized according to site of fistula, associated anomalies and condition of the distal urethra. All the principles of hypospadias surgery should be strictly followed.